Playful Participatory Culture: Learning from Reddit - Massanari, Adrienne (AoIR Selected Papers of Internet Research, 2013)
This project considers how we might understand participatory culture platforms such as Reddit through the lens of game studies. Using ethnographic techniques and approaches from actor-network theory, this research describes several playful patterns of interaction seen commonly on Reddit, and discusses the ways in which certain design choices enable and constrain the kind of play that occurs. I argue that understanding these spaces as games provides a deeper understanding of the interactions between participants and the culture of Reddit at large. It can also help us explore how individuals assign meaning to things like "karma points" and engage in reflexive talk about the rewards and rules governing play. At the same time, this research suggests the “game” of Reddit is not unproblematic, as who can play, how they can play, and what play looks like often reinscribes many hegemonic tendencies of (internet) culture more broadly.